PENGARUH AKUNTABILITAS PUBLIK, PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN DAN STRUKTUR DESENTRALISASI TERHADAP KINERJA APARAT PEMERINTAH DAERAH SKPD DENGAN PENGAWASAN INTERNAL SEBAGAI VARIABEL PEMODERASI KAB. KUANTAN SINGINGI - Ernawilis -; Azwir Nasir; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to test effect of accountability public, participation in budget preparation, the clarity of budget goal, and decentralized structure effect positive partially on local government performance, and to test internal control will moderating effect accountability public, participation in budget preparation, the clarity of budget goal, and decentralized structure effect positive partially on local government performance. This research is survey method. The population in this study is SKPD in the government of Kuantan Singingi regency. The selection the sample with purposive sampling method with total 84 respondents. The data used in this study is primary data. Data was collected by distributed questionnaires. The tecnik of analysis are using multiple linear regression using SPSS 21 sotware.The findings in this study are: accountability publik, participation in budget preparation, the clarity of budget goal, and decentralized structure effect positive partially on local government performance. While the internal control can moderating accountability publik, and participation in budget preparation effect partially on local government performance, and internal control can’t moderating the clarity of budget goal, and structure decentralized effect partially on local government performance.Keywords: Accountability, Budget, Decentralized, Control, and Performance.